The Oxford handbook of Martin Luther's theology - Kolb, Robert (Oxford Univ. Press, 2014)
A brief biographical overview precedes the six sections of this Handbook, designed to give introductions to Luther's thought, its development, and its historical and continuing impact. Presented with a variety of approaches and methods, each of the forty-seven essays gives a summary of its topic, a review of previous studies on the topic, and suggestions for areas of future research.